Arguing with tradition : the language of law in Hopi Tribal court - Richland, Justin B. (Justin Blake), 1970- (Chicago series in law and society., 2008)
Exploring both language and legal issues, this work explains how notions of Hopi tradition and culture shape and are shaped by the processes of Hopi jurisprudence as it comes increasingly to differentiate itself from Anglo-American law.